THE ISSUE OF VALUE IN ECONOMICS: PRACTICAL CONSEQUENCES - Egorov, Dmitry; Michaylova, Yulia; Dyatlov, Yuriy; Makarkina, Oksana; Kolesnikova, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Value is a standard of the cost, a certain common quality, which makes it possible to compare costs of quite different things. This construct probably cannot be operationalized generically, but in the development of theory operationalization is not imperative. Although neoclassical economics rejects this category ultimately, it is possible to demonstrate that this approach can be well adjusted to it. The issue of value is not merely a theoretical one. The purpose of the work is to show that if a feedback through the market must have an objective basis as an initial standard, that is money must have a benchmark, then the correct choice of a monetary benchmark can result in significant positive macro-economic consequences. Methods of research: scientific and philosophical analysis of texts and theoretical development. Conclusions: The idea that the feedback through the market must have an objective basis as an initial standard - that is money must have a benchmark – is not contradictory theoretically and its realization is desirable in practice. An energy monetary benchmark is probably preferable for a modern economy. The energy monetary benchmark can stabilize currency circulation potentially, optimize the price vector and simplify the valuation of mineral resources.